Variables sociodemográficas relacionadas a las estrategias de afrontamiento del paciente con enfermedad oncológica, en el Hospital Regional de Loreto Iquitos, 2019 - Sajami Collantes, Glendy (2024)
The objective was to determine the relationship that exists between sociodemographic variables and coping strategies of patients with Oncological disease, at the Loreto Regional Hospital. The method used was quantitative with a non-experimental descriptive correlational design. The sample included was 70 patients diagnosed with oncological diseases. The technique used was the survey; while the instruments used were the sociodemographic data questionnaire of the patient with oncological disease and the Brief COPE Inventory Questionnaire, coping strategies of the patient with oncological disease. For the bivariate analysis, the non-parametric inferential statistic of free distribution called Chi Square (X2) was used, with a significance level of α 0.05. The results obtained were: 37.1% were between 46 and 60 years old, 78.6% were female, 48.6% reached secondary school, 60% had more than 3 children, The last child of 44.3% of patients was over 25 years old, 55.7% did not have a job, 35.7% had the marital status of cohabitants and, finally, 84.3% presented a moderate level of coping with the disease. In conclusion, a significant relationship was determined between the degree of coping and age (Kendall's Tau-b p= 0.000), number of children (Kendall's Tau-b p= 0.030), level of education (Kendall's Tau-b p = 0.000), age of the last child (Kendall's Tau-b p = 0.015), occupation (Pearson's X2 p= 0.038) and patient's marital status (Pearson's X2 p = 0.008).